Strategies for designing synthetic immune agonists. Issue 4 (11th July 2016) - Wu, Tom Y.‐H.
Summary: Enhancing the immune system is a validated strategy to combat infectious disease, cancer and allergy. Nevertheless, the development of immune adjuvants has been hampered by safety concerns. Agents that can stimulate the immune system often bear structural similarities with pathogen‐associated molecular patterns found in bacteria or viruses and are recognized by pattern recognition receptors (PRRs). Activation of these PRRs results in the immediate release of inflammatory cytokines, up‐regulation of co‐stimulatory molecules, and recruitment of innate immune cells. The distribution and duration of these early inflammatory events are crucial in the development of antigen‐specific adaptive immunity in the forms of antibody and/or T cells capable of searching for and destroying the infectious pathogens or cancer cells. However, systemic activation of these PRRs is often poorly tolerated. Hence, different strategies have been employed to modify or deliver immune agonists in an attempt to control the early innate receptor activation through temporal or spatial restriction. These approaches include physicochemical manipulation, covalent conjugation, formulation and conditional activation/deactivation. This review will describe recent examples of discovery and optimization of synthetic immune agonists towards clinical application. Abstract : Synthetic immune agonists follow design principles different from conventional small‐molecule drugs. Strategies to elicit tissue‐localized innate immune activation are employed to minimize unnecessary systemic inflammation, with the ultimate goal of achieving an antigen‐specific adaptive response. Only by uncoupling efficacy and toxicity can the therapeutic potential of immune agonists be fulfilled in the treatment of cancer, infectious disease and asthma/allergy.